Estrategias de reproducción social de la elite de la ciudad de León en la Edad Moderna - Alfredo Martín García; María José Pérez Álvarez (Nuevo mundo - Mundos Nuevos, 2008)
The objective of this work is to analyze the endogamy practices in the elite of the city of León during Modern Age. This elite was conformed by a few families that controlled most important positions of power, and managed most of the wealth of the province. This combination of political and economic power granted them a preeminent social status in the city. Their aspiration to maintain this privileged position and the fears of losing it, reinforced their endogamy practices as well as other strategies, related to the ecclesiastical career and celibacy.